2009
DOI: 10.1016/j.bbr.2008.10.035
|View full text |Cite
|
Sign up to set email alerts
|

Hunger is the best spice: An fMRI study of the effects of attention, hunger and calorie content on food reward processing in the amygdala and orbitofrontal cortex

Abstract: Research indicates that dysfunctional food reward processing may contribute to pathological eating behaviour. It is widely recognized that both the amygdala and the orbitofrontal cortex (OFC) are essential parts of the brain's reward circuitry. The aims of this fMRI study were (1) to examine the effects of food deprivation and calorie content on reward processing in the amygdala and the OFC, and (2) to examine whether an explicit evaluation of foods is necessary for OFC, but not amygdalar activity. Addressing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
246
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 326 publications
(284 citation statements)
references
References 85 publications
24
246
4
Order By: Relevance
“…In contrast, in a deprived state mainly stimuli predicting a prospective availability lead to the strongest activations. Similar effects were found in a study on food deprivation (Siep et al, 2009); subjects saw pictures of high-or low-calorie food while being either hungry or satiated. The results revealed an increased reward processing in response to low-calorie food in satiated subjects but in response to high calorie food in deprived subjects.…”
Section: Neural Impact Of Additional Stimulisupporting
confidence: 78%
“…In contrast, in a deprived state mainly stimuli predicting a prospective availability lead to the strongest activations. Similar effects were found in a study on food deprivation (Siep et al, 2009); subjects saw pictures of high-or low-calorie food while being either hungry or satiated. The results revealed an increased reward processing in response to low-calorie food in satiated subjects but in response to high calorie food in deprived subjects.…”
Section: Neural Impact Of Additional Stimulisupporting
confidence: 78%
“…For food-reward-related activity to occur in lean individuals, attention to food seems to be necessary, more specifically: the evaluation or imagination of its taste. This was shown by an earlier study from our laboratory 23 in healthy-weight participants after food deprivation and during satiation; this study found that the orbitofrontal cortex (OFC) and the amygdala, both involved in encoding the predictive reward value of stimuli, 24,25 were activated only during taste imagination of high-calorie and low-calorie food pictures and not when judging the orientation of bars presented together with the foods. Likewise, activation of the left lateral OFC in healthy participants depended on whether or not a taste was explicitly evaluated.…”
Section: Introductionmentioning
confidence: 65%
“…When hungry, one is likely to retrieve especially rewarding simulations (based on earlier, highly rewarding eating experiences), in contrast to retrieving less rewarding simulations when satiated. Consistent with this account, research has repeatedly shown that food deprivation and feeling hungry increase reward responses to food, especially to high-calorie food, both in behavioral and neuroimaging studies (Berridge, 1996;Cabanac, 1971;Lavy & van den Hout, 1993;Lozano, Crites, & Aikman, 1999;Raynor & Epstein, 2003;Seibt et al, 2007;Siep et al, 2009;van der Laan, de Ridder, Viergever, & Smeets, 2011). In short, by triggering more rewarding simulations, hunger boosts the perceived attractiveness and choices of palatable, high-calorie foods.…”
Section: Experiments 2: Mindful Attention and The Effects Of Hungermentioning
confidence: 88%